Awake hippocampal synchronous events are incorporated into offline neuronal reactivation - Saichiro Yagi; Hideyoshi Igata; Yuji Ikegaya; Takuya Sasaki (Cell Reports, 2023)
Summary: Learning novel experiences reorganizes hippocampal neuronal circuits, represented as coordinated reactivation patterns in post-experience offline states for memory consolidation. This study examines how awake synchronous events during a novel run are related to post-run reactivation patterns. The disruption of awake sharp-wave ripples inhibited experience-induced increases in the contributions of neurons to post-experience synchronous events. Hippocampal place cells that participate more in awake synchronous events are more strongly reactivated during post-experience synchronous events. Awake synchronous neuronal patterns, in cooperation with place-selective firing patterns, determine cell ensembles that undergo pronounced increases and decreases in their correlated spikes. Taken together, awake synchronous events are fundamental for identifying hippocampal neuronal ensembles to be incorporated into synchronous reactivation during subsequent offline states, thereby facilitating memory consolidation.